MIK2 is a candidate gene of the S-locus for sporophytic self-incompatibility in chicory (Cichorium intybus, Asteraceae) - Palumbo, Fabio; Draga, Samela; Magon, Gabriele; Gabelli, Giovanni; Vannozzi, Alessandro; Farinati, Silvia; Scariolo, Francesco; Lucchin, Margherita; Barcaccia, Gianni (Frontiers in Plant Science, 2023)
The Cichorium genus offers a unique opportunity to study the sporophytic self-incompatibility (SSI) system, being composed of species characterized by highly efficient self-incompatibility (e.g., C. intybus) and complete self-compatibility (e.g., C. endivia). To this end, the chicory genome was used to map seven previously identified SSI locus-associated markers. The region containing the S-locus was therefore restricted to an ~4 M bp window on chromosome 5. Among the genes predicted in this region, MDIS1 INTERACTING RECEPTOR LIKE KINASE 2 (ciMIK2) was particularly promising as a candidate for SSI. Its ortholog in Arabidopsis (atMIK2) is involved in pollen‒stigma recognition reactions, and its protein structure is similar to that of S-receptor kinase (SRK), a key component of the SSI system in the Brassica genus. The amplification and sequencing of MIK2 in chicory and endive accessions revealed two contrasting scenarios. In C. endivia, MIK2 was fully conserved even when comparing different botanical varieties (i.e., smooth and curly endive). In C. intybus, 387 polymorphic positions and 3 INDELs were identified when comparing accessions of different biotypes all belonging to the same botanical variety (i.e., radicchio). The polymorphism distribution throughout the gene was uneven, with hypervariable domains preferentially localized in the LRR-rich extracellular region, putatively identified as the receptor domain. The gene was hypothesized to be under positive selection, as the nonsynonymous mutations were more than double the synonymous ones (dN/dS = 2.17). An analogous situation was observed when analyzing the first 500 bp of the MIK2 promoter: no SNPs were observed among the endive samples, whereas 44 SNPs and 6 INDELs were detected among the chicory samples. Further analyses are needed to confirm the role of MIK2 in SSI and to demonstrate whether the 23 species-specific nonsynonymous SNPs in the CDS and/or the species-specific 10 bp-INDEL found in a CCAAT box region of the promoter are responsible for the contrasting sexual behaviors of chicory and endive.